Kaing Lunggi Bekasad sebagai Artefak Warisan Budaya pada Koleksi Songket Museum Daerah Sambas - Sunandar Sunandar (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study examines in depth the history and development of Kaing Lunggi—the local term for songket cloth—in the Sambas region, West Kalimantan. This study has two main focuses. First, tracing the history of the cloth and textile trade in Southeast Asia that became the background for the entry of external influences into the Sambas region. Second, understanding how Kaing Lunggi emerged, developed, and transformed within the social, economic, and cultural contexts of the local community. Using a historical approach and textile cultural analysis, this study positions Kaing Lunggi as a cultural product born from the dynamics of regional trade since the Sambas Sultanate era. Historical records show that trade networks during that period connected Sambas with major trading centers such as Malacca, Singapore, and the coastal areas of Borneo. Through this route, there was an exchange of raw materials, weaving techniques, and decorative motifs that were then adapted by local artisans. The process of aculturation is visible in Kaing Lunggi motifs that combine local elements with external influences, such as typical Indonesian flora and fauna combined with geometric patterns and typical Malay stylization. The songket weaving technique demonstrates high skill and has been passed down through generations, making it an important part of intangible cultural heritage. Besides its economic value as a trade commodity, Kaing Lunggi also holds a symbolic role. It is worn in various traditional ceremonies, religious celebrations, and as a marker of social status in Sambas society. The use of color, gold thread, and the complexity of the motifs serve as indicators of the wearer's identity and prestige. The results of this study confirm that traditional textiles such as Kaing Lunggi function not only as cultural artifacts but also as active agents in shaping the history and identity of the community. They represent cross-cultural encounters and serve as evidence of the resilience of local traditions amidst globalization.